Hall Mobility of As‐Grown Cu2O Thin Films Obtained Via Electrodeposition on Patterned Au Substrates. Issue 1 (29th November 2017) - Aggarwal, Garima; Das, Chandan; Agarwal, Sumanshu; Maurya, Sandeep K.; Nair, Pradeep R.; Balasubramaniam, K.R.
Abstract : Hall measurement of an electrodeposited Cu2 O film is rendered difficult as the bilayer structure of semiconductor on top of a conductive substrate obviates the measurement. Here, we propose the use of a patterned Au on glass substrate in line/space configuration for the Hall measurement of electrodeposited Cu2 O. A continuous, (111) oriented Cu2 O film was electrodeposited on 8 μm/2 μm Au‐line/space on glass substrate and Hall measurement was performed. The room temperature Hall measurement of the Cu2 O film on the patterned substrate indicates p ‐type conduction with a hole concentration of 2.2 × 10 17 cm −3 and mobility of 4.7 × 10 −3 cm 2 V −1 s −1 . Additionally, the temperature dependent resistivity exhibits a negative slope that is characteristic of a semiconductor. Therefore, the measured electrical characteristics can be attributed to the electrodeposited Cu2 O semiconductor film rather than the conductive substrate. This method can be applied for the Hall measurement of any other electrodeposited semiconductor by optimizing the line/space geometry of the conductive substrate. Abstract : Estimation of the Hall mobility of electrodeposited semiconductors is confounded by the presence of a conductive substrate. Here, the authors demonstrate that patterning the Au substrate in a line/space geometry enables the electrical property measurements of the electrodeposited semiconductor Cu2 O. The simulation of drift‐diffusion equations coupled with Poisson's equation corroborate that the Hall voltage of the Cu2 O sample on patterned Au is attributable to Cu2 O.